Prevalence and Determinant Factors of Intestinal Parasitic Infections and Undernutrition among Primary School Children in North-Central Ethiopia: A School-Based Cross-Sectional Study - Habtye Bisetegn; Habtu Debash; Hussen Ebrahim; Yonas Erkihun; Mihret Tilahun; Daniel Getacher Feleke (Journal of Parasitology Research)
Background. Intestinal parasitic infections (IPIs) are a major public health problem with high morbidity and mortality in developing countries. Undernutrition is a major health problem among school children and affects their cognitive development, psychological development, motor skills, and academic achievements. Therefore, this study aimed to assess the prevalence and determinant factors of IPIs and undernutrition among primary school children. Method. Cross-sectional study was conducted among 450 children from February to March 2021 at selected primary schools in Dessie town, North-central Ethiopia. Participants were selected using a stratified sampling technique. Pretested questionnaires were used to collect sociodemographic and nutrition-related data. Stool samples were used to diagnose IPIs. Participants’ height and weight were measured and body mass index (BMI) was calculated. Nutritional assessment was done using WHO AnthroPlus software. Data were analyzed using SPSS version 26 software. P-values <0.05 were considered statistically significant. Result. The overall prevalence of intestinal parasites was 28.9%. The prevalence of intestinal protozoa and helminths were 19.1% and 9.8%, respectively. Entamoeba histolytica/dispar was the most prevalent parasite (9.3%) followed by Giardia intestinalis (7.6%), Enterobius vermicularis (2.9%), and Ascaris lumbricoides (2.7%). The prevalence of intestinal parasites was higher in male (16.5%) than in female (12.4%) participants. Children whose mother’s level of education is illiterate, 6–11 years old, have a habit of eating raw/undercooked fruits and vegetables, untrimmed and dirty fingernails, and sickness in the past week were significantly associated with IPIs. The prevalence of underweight, stunting, and wasting were 22.4%, 26.2%, and 20.7%, respectively. Multivariable logistic regression showed gender, family size, meal frequency, and breakfast were significantly associated with undernutrition. IPIs had a statistically significant association with underweight, stunting, and wasting. Conclusion. The study showed that IPIs and undernutrition are still major health problems among children in North-central Ethiopia. Periodic deworming, community health, and school health education will be valuable to improve the health, growth, and educational outcome of children.